2010
DOI: 10.3155/1047-3289.60.10.1257
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chromium-Doped Malayaite Pigments from Wastewater Containing Low Chromium(VI)

Abstract: A malayaite pigment was synthesized with wastewater containing low chromium (Cr)(VI) by a novel liquidphase reaction method. The effects of the particle size of the precursor and calcination temperature on the final product are examined. The result of scanning electron microscopy shows that the obtained precursor is amorphous and the particle size is approximately 250 nm. The results of X-ray diffraction and differential scanning calorimetry show that the complete transformation temperature was approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…A broad, intense peak centered at around 500-550 nm (18180 cm -1 ) could be ascribed to the spin allowed 3 T 1 ↔ 3 T 2 transition of octahedral Cr 4+ (Lopez-Navarrete et al 2003). This similar peak was also reported by Lee and Lee (2008a) and Zhang et al (2010). A drop at around 650 nm is typical of the 3d 3 ions which are from the anti-crossing of the spin forbidden 1 E and 1 t 2 levels (Lopez-Navarrete et al 2003).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…A broad, intense peak centered at around 500-550 nm (18180 cm -1 ) could be ascribed to the spin allowed 3 T 1 ↔ 3 T 2 transition of octahedral Cr 4+ (Lopez-Navarrete et al 2003). This similar peak was also reported by Lee and Lee (2008a) and Zhang et al (2010). A drop at around 650 nm is typical of the 3d 3 ions which are from the anti-crossing of the spin forbidden 1 E and 1 t 2 levels (Lopez-Navarrete et al 2003).…”
Section: Resultssupporting
confidence: 70%
“…This result was likely associated with phase formation of malayaite which has been widely known to be occurring at very high temperatures. Zhang et al (2010) also reported an intense exothermic peak at 1065.6°C which was likely be related to crystallization or transformation process. From both TGA and DTA results, the gels were calcined at ≥ 1000°C.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The chrome resources can be recovered from remaining ashes and reused for industrial production [14,15]. In recent decades, the ceramic pigments prepared from the chromium-rich sludge are widely investigated [16,17]. Jesionowski et al [18] used post-galvanic waste solutions from a chromating process as raw material to prepare the green pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several researchers investigated the synthesis of inorganic black iron-chromite pigment with iron-or chromium-containing industrial wastes, and thereafter it was introduced into the ceramic matrix to produce black ceramic tiles (Tanisan and Turan, 2011;Hajjaji et al, 2011;Costa et al, 2008;Chen et al, 2015;Zhang et al, 2010;Zhang et al, 2014). Tanisan and Turan (2011) reported that the black porcelain tile can be prepared with less expensive pigments through sintering a mixture of 40% natural chromite and 60% iron-containing oxide waste from the steel rolling mill at 1200 ºC.…”
Section: Introductionmentioning
confidence: 99%